Prevalence Of Eimeria Spp. Infection In Broiler Farming (Gallus Domesticus) - Chintia Prastika Dewi (Magenta Journal De Healthymedi, 2025)
Coccidiosis remains one of the most economically significant parasitic diseases affecting broiler production worldwide. This study aimed to determine the prevalence of Eimeria spp. infection and identify the morphological characteristics of oocysts detected in broiler chickens raised in Kalibaru District, Banyuwangi Regency, Indonesia. A cross-sectional study was conducted using 75 fecal samples collected from five commercial broiler farms. Samples were examined using the flotation technique followed by microscopic identification based on oocyst morphology and morphometric measurements. The results revealed that all examined samples were positive for Eimeria spp, resulting in a prevalence rate of 100%. Both sporulated and non-sporulated oocysts were observed, indicating active parasite transmission within the farming environment. Morphological observations suggested the presence of multiple Eimeria species, including E. tenella, E. necatrix, E. maxima, E. acervulina, E. praecox, and E. mitis. These findings contribute to regional disease surveillance and support the development of evidence-based biosecurity and coccidiosis control strategies.